2005
DOI: 10.1536/ihj.46.939
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Differences in the Delivery of Cardiac Management to Women Versus Men With Acute Myocardial Infarction in Japan Tokai Acute Myocardial Infarction Study: TAMIS

Abstract: SUMMARYIt is of concern that women are more likely to undergo fewer diagnostic tests and receive less treatment for acute myocardial infarction (AMI) than men. However, it is still unclear whether gender differences exist according to age groups. Therefore, we studied the influence of gender on the delivery of cardiac management according to two age groups (< 65, 65) in Japan. Data from the Tokai Acute Myocardial Infarction Study (TAMIS) sample were used. This is a retrospective study of all consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
3
4
0
Order By: Relevance
“…These results were consistent with previous studies suggesting that older age, 1,[6][7][8] female gender, [9][10][11][12] and dementia 13) are factors inversely related to the use of invasive procedures including PCI. Increased ADL impairment in the patients without emergency PCI may have been due to the greater age of this subgroup.…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with previous studies suggesting that older age, 1,[6][7][8] female gender, [9][10][11][12] and dementia 13) are factors inversely related to the use of invasive procedures including PCI. Increased ADL impairment in the patients without emergency PCI may have been due to the greater age of this subgroup.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with TAMIS, 13) the TAMIS-II data did not suggest that being female contributed to UCG or TMT use. The underuse of TMT among women may not be problematic in Japan.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, the effect of gender on the in-hospital management of patients with AMI remains controversial. 1,[4][5][6][7][8][9][10][11][12] In addition, our previous retrospective study, TAMIS,13) demonstrated that the gender differences in AMI management are different between younger and older populations, which is consistent with the findings of another study.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Fifteen hospitals then approved the study. Thirteen out of the 15 hospitals that participated in TAMIS, 7) which was a retrospective version of TAMIS-II, were included in TAMIS-II. All 15 hospitals that participated in TAMIS-II were nonprofit general hospitals that were capable of performing coronary angiography (CAG) and percutaneous coronary intervention (PCI).…”
Section: Methodsmentioning
confidence: 99%